2021
DOI: 10.3847/1538-4357/abe1b9
|View full text |Cite
|
Sign up to set email alerts
|

Connection between Galaxies and H i in Circumgalactic and Intergalactic Media: Variation according to Galaxy Stellar Mass and Star Formation Activity

Abstract: This paper systematically investigates the comoving megaparsec-scale intergalactic medium (IGM) environment around galaxies traced by the Lyα forest. Using our cosmological hydrodynamic simulations, we investigate the IGM–galaxy connection at z = 2 by two methods: (i) cross-correlation analysis between galaxies and the fluctuation of Lyα forest transmission (δ F) and (ii) comparison of the overdensity of neutral hydrogen (H i) and galaxies. Our simulations reproduce observed cross-correlation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…Several groups have already demonstrated the feasibility of this approach (e.g., Lee et al 2014Lee et al , 2018Cai et al 2016;Mukae et al 2020), and massive protoclusters at redshifts z = 2 − 3 have been identified (Lee et al 2016;Cai et al 2017). Moreover, this technique enables the derivation of the correlation between galaxy overdensity and Hi overdensity, providing valuable insights into the relationship between galaxies/AGNs and the surrounding Hi gas (Mukae et al 2017;Liang et al 2021;Momose et al 2021).…”
Section: Probing the Impact Of Feedback By Cosmological Simulationsmentioning
confidence: 98%
“…Several groups have already demonstrated the feasibility of this approach (e.g., Lee et al 2014Lee et al , 2018Cai et al 2016;Mukae et al 2020), and massive protoclusters at redshifts z = 2 − 3 have been identified (Lee et al 2016;Cai et al 2017). Moreover, this technique enables the derivation of the correlation between galaxy overdensity and Hi overdensity, providing valuable insights into the relationship between galaxies/AGNs and the surrounding Hi gas (Mukae et al 2017;Liang et al 2021;Momose et al 2021).…”
Section: Probing the Impact Of Feedback By Cosmological Simulationsmentioning
confidence: 98%
“…On the other hand, the HI and dust column densities should be sufficiently low that we can observe their Lyα emission and identify the structure of LAEs (e.g., Shimakawa et al 2017a). In fact, several studies reported that the large-scale (tens of Mpc) HI gas traced by Lyα absorption is associated with high-density structures of LAEs (Cucciati et al 2014;Mawatari et al 2017;Liang et al 2021), while the high optical depth of Lyα emission could lead to a deficit of LAEs at small scales (e.g., Momose et al 2021aMomose et al , 2021b. The most massive galaxies with M s > 10 11 M e in the 53W002 field tend to avoid high-density peaks of LAEs, but they show similar wide distribution along the SW-NE direction (Figure 15).…”
Section: Comparisons With Previous Studiesmentioning
confidence: 99%
“…These studies have examined the galaxy-H I correlation at small separations to constrain the spatial extent, kinematics, and temperature of inflows and outflows in the circumgalactic region. At separations well beyond ∼1 cMpc (comoving Mpc), on the other hand, the correlation is instead dominated by large-scale structure and is expected to depend mainly on the halo mass (Momose et al 2021b). Kim & Croft (2008) made an initial estimate of the halo mass of LBGs based on the surrounding Lyα absorption, although the data of Adelberger et al (2003) permitted only loose constraints with an uncertainty of 0.6 dex.…”
Section: Introductionmentioning
confidence: 99%